2004
DOI: 10.1103/physrevstab.7.050702
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic permanent magnet undulators

Abstract: In order to obtain high magnetic fields in a short period undulator, superconductive undulators have been actively investigated in recent years. In this paper, however, we propose a new approach, the cryogenic permanent magnet undulator (CPMU) design, using permanent magnets at the cryogenic temperature of liquid nitrogen or higher. This cryogenic scheme can be easily adapted to currently existing in-vacuum undulators and it improves the magnetic field performance by 30%-50%. Unlike superconductive undulators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(86 citation statements)
references
References 14 publications
0
85
0
1
Order By: Relevance
“…It has been suggested that for hybrid types the saturation field strength in the ferromagnetic pole material can be increased by simultaneously replacing the Co steel by dedicated materials such as dysprosium [27]. Superconducting technology on the other hand has not yet reached mm-scale period length with the desired field strength.…”
Section: Status and Perspectivesmentioning
confidence: 99%
“…It has been suggested that for hybrid types the saturation field strength in the ferromagnetic pole material can be increased by simultaneously replacing the Co steel by dedicated materials such as dysprosium [27]. Superconducting technology on the other hand has not yet reached mm-scale period length with the desired field strength.…”
Section: Status and Perspectivesmentioning
confidence: 99%
“…the widespread Apple-IIs [29], and (c) in-vacuum undulators (IVIDs) [30], now standard in many synchrotrons. Under development are (a) new varieties of polarizing undulators, (b) quasi-periodic devices, (c) cryogenic PMs [30,31], and (d) superconducting undulators (SCUs), including planar designs and beyond [33]. Undulator designs specific for FELs and ERLs, but unsuitable for storage rings include (a) those with poles close to beam horizontally, e.g.…”
Section: Present Statusmentioning
confidence: 99%
“…R&D resources thus far invested in SCUs are an order of magnitude less than that devoted to IVIDs before their acceptance in third generation synchrotron facilities, and are significantly less than has been devoted recently to cryogenic permanent magnet systems in Europe, Japan and even the US [31,32,4143]. Though the family of noncryogenic PM devices is already poised to serve as baseline design options for future light sources, it would nonetheless be prudent to expedite SCU R&D to enable ultimate performance potential of future light sources.…”
Section: Undulator Technology Options For Future Light Sourcesmentioning
confidence: 99%
“…As the PM and pole-piece materials, NEOMAX-53CR and Permendur (NEOMAX Co., Ltd) are assumed, respectively. NEOMAX-53CR, made from praseodymiumiron-boron, has the remanent field of 1.5 T at 77 K [13], and Permendur has the saturation magnetic flux density of 2.39 T [20]. Note that the pole length (L p ) and the thickness of the superconductor (T s ) determine the volume of the fraction of the permanent magnet to be removed.…”
Section: Examplementioning
confidence: 99%
“…The current trend in undulator developments is toward shortening the magnetic period to obtain SR with shorter wavelength [5][6][7][8]. Therefore, much effort has been made to develop short period undulators such as an in-vacuum undulator [9,10], a superconducting undulator (SCU) working around liquid helium temperature [11,12], and a cryogenic permanent magnet undulator (cryoundulator) [13]. The last one has been recently proposed at SPring-8, which utilizes PMs under cryogenic environment.…”
Section: Introductionmentioning
confidence: 99%